Hydrogen Bond Directed Photocatalytic Hydrodefluorination; Overcoming Electronic Control - Khaled, Mohammad B. (J Am Chem Soc, 2017)
The photocatalytic C–F functionalization of highly fluorinated arenes is a powerful method for accessing functionalized multifluorinated arenes. The decisive step in the determining regioselectivity in fluorine functionalization is fluoride fragmentation from the radical anion of the multifluorinated arene. To date, the availability of regioisomers has been dictated by the innate electronics of the fluorinated arene, limiting the synthetic utility of the chemistry. This study investigates the remarkable ability of a strategically located hydrogen bond to transcend the normal regioselectivity of the C–F functionalization event. A significant rate acceleration is additionally observed for hydrodefluorination of fluorines that can undergo intramolecular hydrogen bonds that form 5–8 membered cycles with moderately acidic N–Hs. The hydrogen bond is expected to facilitate the fragmentation not only by bending the C–F bond of the radical anion out of planarity, but also by increasing the exothermicity of the fluoride extrusion step through protonation of the naked fluoride. Finally, the synthetic utility of the method is demonstrated in an expedited synthesis of the trifluorinated α-phenyl acetic acid derivative required for the commercial synthesis of Januvia, an anti-diabetic drug. This represents the first synthesis of a commercially important multifluorinated arene via a defluorination strategy, and is significantly shorter than the current strategy.